A qualitative study of multiphase steel microstructure developed in four different steel alloys - khraisat, walid (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In this work, quench and partitioning (Q&P) heat treatment was performed on four different steel alloys in order to obtain multiphase steels having a microstructure containing ferrite, martensite, bainite, and retained austenite. The four alloys are SS1672, 38MnVS6, R350HT and SS2244. They are chosen to study the effect of increasing the Mn/Si ratio and the Cr effect on the microstructure. Multiphase steels with retained austenite of different fractions and morphologies in a ferritic-bainitic matrix have been obtained depending on the Cr and Si amounts. Detailed characterisation of the microstructural evolution of Q&P heat-treated four steel alloys by optical microscopy (OM) was done only to provide a qualitative understanding. Despite these limitations, the OM micrographs were sufficient to confirm and identify the formed phases, especially the bainite phase. It is found from this work that high Si levels are not strictly necessary to prevent pearlite formation during the Q&P treatment of medium and eutectoid steels, due to the presence of manganese. A Mn/Si ratio greater than 2 is found to be necessary to prevent pearlite formation. Also, a lower martensite start temperature (Ms) leads to a significant refinement of the microstructure components bainite and retained austenite.